Troubling National Discourses in Anti‐Racist Curricular Planning - Schick, Carol; St. Denis, Verna (Canadian Journal of Education/Revue canadienne de l'éducation, 2005)
The narrative of the Canadian prairie context is invested in intercultural relations that privilege whiteness and marginalize Aboriginal people and other racial minorities. We maintain that anti‐oppressive curriculum on the Canadian prairies must examine how racial identifications are constructed through commonplace national discourses. A curriculum that is anti‐oppressive needs to examine the production of racial identifications, including the construction of whiteness in a Canadian context, where racism often exists in denial. Without a critical race analysis, the “celebration of diversity” and other popular narratives have every possibility of reinforcing relations of domination. Key words: anti‐oppressive education, Aboriginal education, critical whiteness studies Les textes au sujet des Prairies canadiennes font surtout état de relations interculturelles qui privilégient les Blancs et marginalisent les peuples autochtones et les autres minorités ethnoculturelles. Selon les auteures, il faut analyser le mode de construction des identités ethnoculturelles à travers les discours nationaux très répandus. Un programme scolaire qui se veut antioppressif doit tenir compte du processus de production identitaire, notamment chez les eurocanadiens où le racisme existe souvent, même s’il est nié. Sans une analyse critique portant sur l’identité ethnoculturelle, la promotion de la diversité et les autres discours populaires risquent fort de renforcer les relations de domination. Mots clés : éducation antioppressive, éducation dispensée aux autochtones, études critiques sur les eurocanadiens.